Disabled people - rehabilitation with sport - Łosień, Tomasz; Mędrak, Anna; Bajerska, Izabela; Plaskacz, Paweł; Cebula, Aleksandra; Kniaziew-Gomoluch, Katarzyna (Journal of Education, Health and Sport, 2017)
Sport was used to complement therapy in original form, improve of motor patterns and reeducate functions of people with disabilities. With a passing of time, sport evolved to integrated part of rehabilitation as an element of improvement. Moreover, he became as a tool to improve the social integration of people which finished the treatment or/and have deficits. We can notice the huge sport development of people with disabilities, which was initiated by Sir Ludwig Guttmann’s who claimed that view of sport is equal for people with disabilities and able-bodied people. The quality of physical activity of people with disabilities is indicated by motor preparation, training and sport (wellness, nutritionist, sport and exercise psychologist) which currently is all the same except individual approach to particular dysfunction of the person with disability. Sport allow to develop not only physical sphere, but also teaches social integration, teamwork skills, self-discipline, improves the quality of life and outcome of the ADL scale (activities of daily living scale) of people with disabilities which do sport actively. The variety of sports disciplines and ability to use appropriate orthopedic stuff allows to activate people with every kind of disabilities and dysfunction.